Analysis and Modeling of Generic Mac Protocols in Wireless Sensor Network - R Sheelavantar, Praneeta; A Joshi, Shreedhar; A Bidkar, Gopal (International Journal of Engineering and Technology, 2018)
Nowadays Wireless Sensor Networks are used everywhere, which plays an important role in recording the physical conditions of the environment and organizing the data collected at a central location. WSN has many applications in fields such as military, home automation, industries, commercial, battle field, food safety etc. This paper presents the analysis of Generic MAC Protocols with different routing protocols using Qualnet 7.4 simulator. The simulation result shows that comparing with other MAC protocols SLOT CSMA/CA gives better performance. Total unicast message sent, received, average end-to-end delay, average jitter, average throughput, energy consumed, packets received and lost are analysed for each routing protocol.Â Â
Keywords: CSMA; CSMA/CA; SLOT CSMA; SLOT CSMA/CA; QualNet.